Предмет: Математика,
автор: glibzlochevskiy
Як вирішити -4(2k-9)-3(6k+1) повне пояснення
miki68:
=-8k+36-18k-3=-26k+33
Ответы
Автор ответа:
3
Ответ:
-4(2k-9)-3(6k+1)=-8k+36-18k-3= -26k+33
Автор ответа:
2
Пошаговое объяснение:
-4(2k-9)-3(6k+1)= -4×2k-4×(-9)-3×6k-3×1= -8k+36-18k-3= -26k+33
Похожие вопросы
Предмет: Русский язык,
автор: ФедяМакс
Предмет: Русский язык,
автор: света19863
Предмет: Русский язык,
автор: morozovama76
Предмет: Математика,
автор: 19840308402439
Предмет: Информатика,
автор: Hogig